Penentuan Tarif Layanan Kesehatan Gigi dan Mulut dengan Metode Activity Based Cost System - Dinik Fitri Rahajeng Pangestuti; Indah Purbasari (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2019)
Background: The result of the morbidity report at 2001, shown that dental and oral health in Indonesia is still become public complaint, it is around 60%, such as dental caries and periodontal disease. Dental public health effort to date has yet to be run with optimal due to various constraints, including: limitations of the power, the means of operating costs as well as social and economic conditions of society. Considering these constraints have developed a model of services in the form of a layered service (level of care) according to existing resources, in the form of Primary Health Care (PHC). But this time the tariff is determined by hospitals, especially the private hospitals are still considered high by most of society. In determining the cost of products as the basis for determining the price of the hospital sometimes still use traditional accounting systems that pricing anyway no longer reflects the activity because of the many categories that are not direct. The main difference between the calculation of the product cost of goods of traditional cost accounting by activity-based costing is the amount of cost driver (trigger) is used. In the determination of cost of products with activity-based costing uses the cost drivers in the sum more than in traditional cost accounting systems that use only one or two cost drivers based on the unit.Objective: To determine the differences between determination of dental and oral health service tariff by using Activity Based Cost System and traditional method.Methods: This research was a case study research and how to collect data from the financial reporting RSUD Panembahan Senopati Bantul about patient visits for examination in dental health polyclinic. Results: The results of this research were the determination of the tariff model of oral health services by using Activity-Based Cost systems, as well as a comparison between traditional fare tariffs and tariff system for Activity Based Cost System. Keywords: tariff, dental and oral health, Primary Health Care, activity based costing, cost driver.